Pengaruh Lingkungan Kerja, Stres Kerja Terhadap Kepuasan Kerja Karyawan Pada Pabrik Rokok Tunas Mandiri Unit Lorok Kabupaten Pacitan - Restu Impiyaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The study discusses the Effect of the Work Environment, Work Stress on Employee Job Satisfaction at the Tunas Mandiri Cigarette Factory, Lorok Unit, Pacitan Regency. This study used a quantitative method with a total of 70 employees, taking this sample by using the slovin formula. The application used to test this research uses IBM SPSS 26. Data analysis techniques use multiple linear regression analysis, validity test, reliability test, classical assumption test, hypothesis testing and multiple determinant analysis (R2). The results of the study show that the t-test was carried out partially, that the Work Environment variable has a positive and significant effect on Employee Job Satisfaction, the Job Stress variable has a positive and significant effect on Employee Job Satisfaction. And regarding the F test shows that the variables Work Environment and Work Stress simultaneously affect Employee Job Satisfaction at the Tunas Mandiri Cigarette Factory, Lorok Unit, Pacitan Regency.